EVALUASI PRODUKTIVITAS DAN OPTIMASI PENGGUNAAN PERALATAN MEKANIS PADA PEKERJAAN CUT AND FILL - Hendra Kundrad SR; Minson Simatupang; Sudarsono Sudarsono (Jurnal Manajemen Rekayasa (Journal of Engineering Management), 2021)
Earthworks is one of the most vital parts in a large scale construction project. Generally, earthworks is carried by heavy equipment in order to make it easier for human to do their jobs so that the results can be achieved more easily in short time. The management of heavy equipment is very important to support the running of the job. This study is aims to determine how much the productivity, cost and time and also to optimize the heavy equipment usage costs. Determination of the optimum solution was carried out using integer linear programing of branch and bound method. The optimum solution obtained in earth excavation work used 1 unit of excavator with a production capacity of 29,36  and 1 unit of dump truck with a production capacity 25,82 , the required cost of Rp.62.721.260,00 or 45,23% is lower than the original cost of Rp.114.515.748,00. While for stone quarrying work used 1 unit excavator + rock drill breaker with a production capacity of 13,39  and dump truck with a production capacity of 16,99  the required cost of Rp.62.721.260,00 or 45,23% is lower than the original cost of Rp.114.515.748,00. Keywords :Heavy Equipment, Productivity, Optimum, AILP, Branch and Bound